Analysis of Individual and Behavioral Factors Affecting the Success of Pulmonary Tuberculosis Treatment at Sukaramai Public Health Center, Pakpak Bharat Regency - Rusmiaty Sinaga; Reni Aprinawaty Sirait; Desideria Yosepha Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Pulmonary tuberculosis (TB) remains a major global public health problem, with suboptimal treatment success rates in many regions. This study aimed to analyze individual and behavioral factors affecting the success of pulmonary TB treatment at Sukaramai Public Health Center, Pakpak Bharat Regency. This study employed an analytical observational design with a cross-sectional approach. The population consisted of 328 TB patients, with a sample of 180 respondents selected using purposive sampling. The variables studied included age, sex, education, knowledge, and medication adherence. Data were analyzed using univariate, bivariate (Chi-square test), and multivariate (logistic regression) analyses with a significance level of 0.05. The results showed that most respondents were aged >40 years (63.9%), female (56.7%), had low education levels (71.1%), and had poor knowledge (50.6%). Medication adherence was relatively good, with 59.4% of respondents classified as adherent. Bivariate analysis indicated significant associations between knowledge (p=0.002) and medication adherence (p=0.019) with treatment success. However, multivariate analysis revealed that only medication adherence had a significant effect on treatment success (OR=3.12; 95% CI: 1.65–5.90; p=0.001), while knowledge was not statistically significant. In conclusion, medication adherence is the most dominant factor influencing the success of pulmonary TB treatment. Therefore, interventions should focus on improving patient adherence through continuous health education, family support, and strengthening treatment supervision systems to enhance treatment outcomes.